2017
DOI: 10.1111/jav.01456
|View full text |Cite
|
Sign up to set email alerts
|

Tasting novel foods and selecting nutrient content in a highly successful ecological invader, the common myna

Abstract: Invasion success is dependent on the ability of a species to discover and exploit novel food resources. Within this context, individuals must be willing to taste novel foods. They must also be capable of evaluating the nutritional content of new foods, and selecting their relative intake in order to fulfil their nutritional needs. Whereas the former capacity is well studied, little is known about the latter capacity. First, using the common myna as a model avian invader species, we quantified the willingness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Moreover, protein‐deprived mynas selectively consumed novel foods containing higher proportions of protein (Peneaux et al . 2017). Urban habitats may therefore be deficient in protein‐rich foods, making this macronutrient a potentially limiting resource for ornamental production.…”
Section: Carotenoid Displays As Bio‐indicators Of Environment Qualitymentioning
confidence: 99%
“…Moreover, protein‐deprived mynas selectively consumed novel foods containing higher proportions of protein (Peneaux et al . 2017). Urban habitats may therefore be deficient in protein‐rich foods, making this macronutrient a potentially limiting resource for ornamental production.…”
Section: Carotenoid Displays As Bio‐indicators Of Environment Qualitymentioning
confidence: 99%
“…The second study, performed on captured urban mynas in outdoor aviaries, revealed intra‐specific differences in foraging preferences, where those that selected high‐protein foods were more exploratory and more rapidly solved foraging tasks than conspecifics that selected high‐carbohydrate foods (Peneaux et al. ). These findings showed the ability of this species to evaluate the nutritional content of foods, suggesting that this mechanism might be important to their ecological success as invaders.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…For example, expanding our understanding of the role of nutrition as a modulator of cognitive abilities in birds would be a powerful approach to better comprehending relevant successes or failures of urban birds (Peneaux et al. ). Our knowledge of the relationships between cognition and nutrition is mostly derived from studies of rodents, non‐human primates, and humans (Wahl et al.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…It may also help us to determine what nutrients may be limiting for a particular species in natural habitats (Coogan et al ., ; Aryal et al ., ; Coogan et al ., ). Such analyses have, for example, been made on several mammal and bird species (Panthi et al ., ; Peneaux et al ., ; Coogan et al ., ).…”
Section: Introductionmentioning
confidence: 98%